Internal processes in power semiconductors at virtual junction temperature measurement. (September 2016) - Chen, W.; Franke, J.; Herold, C.; Bhojani, R.; Lutz, J.
Abstract: High measurement accuracy is the basis for a precise determination of the junction temperature Tj . Temperature measurement can be performed by means of temperature sensitive parameters (TSP) using the VCE (T)-method, however, internal semiconductor processes like the removal of stored charge in bipolar devices have to be respected. The aim of this work is to determine the earliest time point of accurate measurement tMD after switching off, as well as dependencies on device voltage classes and applied battery voltage. Measurement results are confirmed by performing the simulation with Sentaurus TCAD. Dependencies of delay tMD on temperature, applied measurement current and battery voltage are demonstrated for IGBT and silicon diode. Highlights: Internal processes in power semiconductors have to be respected for precise junction temperature measurement. The occurrence of tMD relies on the removal of the stored charge carriers in bipolar devices after switching off. Measurement current, temperature and battery voltage influence the measurement delay. The single pulse measurement results were confirmed by TCAD simulation.